Программа школы основ марксизма-ленинизма (Система партийной учебы, 1969)
Экземпляры: УКП (20220211) / Инвентарный номер: АП19690110 / Сис.шифр: 66.69(2) / Авт.знак: П 78 / ГРНТИ: 11 / ББК: 66.69(2)КПСС,5